2012
DOI: 10.5937/sjecr13-2328
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an adapted basketball training program on the physical fitness of adolescents with mental retardation: A pilot study

Abstract: Introduction: Previous studies have established a direct connection between levels of physical fitness and the time needed to perform daily tasks in adults with intellectual disabilities. These findings indicate that physical activity can improve the quality of life of individuals with intellectual disabilities. The aim of this pilot study was to evaluate the effects of an eight-week specially adapted basketball training program on the physical fitness of adolescents with mental retardation. Methods: Twelve ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Our findings suggest that the 12-week PA intervention can improve the 6MWT distance (partial η 2 = 0.149), which is consistent with our previous findings from a systematic review and meta-analysis for children with ID [15]. In that systematic review and meta-analysis, seven out of eight PA interventions employing the 6MWT reported effective results on cardiopulmonary fitness [18,29,[33][34][35][36][37] (partial η 2 = 0.010-0.600). Among those reporting effective (including this study), the interventions with vigorous intensity (compared with moderate intensity), those following the progression principle (compared with constant intensity), and those combined aerobic and resistance training (compared with aerobic training only) tended to generate larger effect sizes (partial η 2 > 0.14) [18,29,33,35].…”
Section: Hrpf-related Outcomessupporting
confidence: 89%
“…Our findings suggest that the 12-week PA intervention can improve the 6MWT distance (partial η 2 = 0.149), which is consistent with our previous findings from a systematic review and meta-analysis for children with ID [15]. In that systematic review and meta-analysis, seven out of eight PA interventions employing the 6MWT reported effective results on cardiopulmonary fitness [18,29,[33][34][35][36][37] (partial η 2 = 0.010-0.600). Among those reporting effective (including this study), the interventions with vigorous intensity (compared with moderate intensity), those following the progression principle (compared with constant intensity), and those combined aerobic and resistance training (compared with aerobic training only) tended to generate larger effect sizes (partial η 2 > 0.14) [18,29,33,35].…”
Section: Hrpf-related Outcomessupporting
confidence: 89%
“…Slight physical fitness results of both groups of respondents at the initial and final testing show that the ID has an impact on performance reduction in relation to persons without disabilities (18). The cause of this phenomenon should also be sought in previously documented studies that show that adolescents with IDs are less active than their peers without disabilities (13) ( Table 2).…”
Section: Discussionmentioning
confidence: 85%
“…Ten studies included both male and female participants [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies included both male and female participants [47][48][49][50][51][52][53][54][55][56]. Five studies included male participants [57][58][59][60][61].…”
Section: Characteristics Of Participants With Intellectual Disabilitiesmentioning
confidence: 99%